Vitamin D insufficiency and deficiency are associated with a higher level of serum uric acid: A systematic review and meta-analysis - Nipith Charoenngam (2020)
© 2019, © 2019 Japan College of Rheumatology. Introduction/objectives: Several epidemiological studies have suggested that patients with vitamin D insufficiency and deficiency tend to have a higher level of serum uric acid compared with those with adequate vitamin D level although the results were inconsistent across the studies. The current systematic review and meta-analysis was conducted with the aim to summarize all the available data. Methods: A systematic review was conducted using MEDLINE and EMBASE database from inception to May 2018 to identify all studies that compared the level of serum uric acid between individuals with normal vitamin D level and patients with vitamin D insufficiency/deficiency. Eligible studies must be cohort or cross-sectional studies that consisted of two groups of adult participants, one with normal level of vitamin D (vitamin D level >30 ng/ml) and one with vitamin D insufficiency (vitamin D level 20–30 ng/ml) or vitamin D deficiency (vitamin D level of <20 ng/ml). Mean serum uric acid level and standard deviation of participants were extracted from each study to calculate mean difference (MD). Pooled MD was then calculated by combining MDs of each study using random-effects model. Results: A total of seven cross-sectional studies were eligible for the meta-analyses. Individuals with normal vitamin D level had a significantly lower serum uric acid level than patients with vitamin D insufficiency with the pooled MD of –0.33 mg/dl (95%CI, –0.61, –0.04), and also had a significantly lower serum uric acid level than patients with vitamin D deficiency with the pooled MD of –0.45 mg/dl (95%CI, –0.82, –0.08). The statistical heterogeneity of these meta-analyses was high with the I 2 of 78% and 89%, respectively. Funnel plots of both meta-analyses were fairly symmetric and did not provide a suggestive evidence for the presence of publication bias. Conclusion: Both patients with vitamin D insufficiency and patients with vitamin D deficiency had a significantly higher level of serum uric acid compared with individuals with normal vitamin D level.